Translating Brand Authenticity and Brand Experience Into Brand Loyalty: The Mediating Role of Brand Trust in Starbucks - Alexandra Josephine; Charly Hongdiyanto (Journal of Accounting and Finance Management, 2026)
In this growing and highly competitive market, coffee brands needed to start building a trustworthy relationship with their customers. This is important to make sure that brand has loyal customers, which is a major part of having a successful business. This research is done to understand some key factors, for example, brand authenticity, brand experience, brand loyalty, and it relates. Brand trust is also used as the mediating factor for each connection. This research utilizes a quantitative approach by disseminating online questionnaires to 260 respondents across Java. Data were later processed through PLS-SEM where the result shows that brand authenticity and brand experience correlates positively with brand trust and loyalty. Brand trust is also seen to hold a positive effect on brand loyalty through its mediation role. These findings show that customers’ trust is essential to deliver brand authenticity and experience to customers’ loyalty. Overall, this study emphasized the relevance of building trust to enhance brand loyalty in terms of coffee brands around Java.